Loss of Muscle Mass Induced by Aging (2019)
Introduction: The world population ages rapidly, understanding the anatomo-functional changes of the muscle allows the implementation of effective actions in this age group. The objective of this work was to identify, through a review of scientific literature, the current advances in the molecular processes related to the loss of muscle mass induced by aging. Materials and methods: The molecular causes of muscle mass loss induced by aging were reviewed through scientific articles from 2006 to 2016 on the Pubmed, Scielo and PEDro databases, combining the terms muscular aging, exercise and physical therapy. Results: Three sections were determined: 1) sarcopenia and aging, 2) molecular pathways of muscle mass loss induced by aging and 3) aging, exercise and functionality. Conclusion: Knowing the molecular basis of muscle mass loss induced by aging allows the physiotherapist to understand, evaluate and intervene related mechanisms to perform actions that improve the functionality and quality of life of older adults.